Targeting glutamine metabolism enhances tumor-specific immunity by modulating suppressive myeloid cells - Oh, Min-Hee; Sun, Im-Hong; Zhao, Liang; Leone, Robert D; Sun, Im-Meng; Xu, Wei; Collins, Samuel L; Tam, Ada J; Blosser, Richard L; Patel, Chirag H; Englert, Judson M; Arwood, Matthew L; et al. (The Journal of clinical investigation, 2020)
Myeloid cells comprise a major component of the tumor microenvironment (TME) that promotes tumor growth and immune evasion. By employing a small-molecule inhibitor of glutamine metabolism, not only were we able to inhibit tumor growth, but we markedly inhibited the generation and recruitment of myeloid-derived suppressor cells (MDSCs). Targeting tumor glutamine metabolism led to a decrease in CSF3 and hence recruitment of MDSCs as well as immunogenic cell death, leading to an increase in inflammatory tumor-associated macrophages (TAMs). Alternatively, inhibiting glutamine metabolism of the MDSCs themselves led to activation-induced cell death and conversion of MDSCs to inflammatory macrophages. Surprisingly, blocking glutamine metabolism also inhibited IDO expression of both the tumor and myeloid-derived cells, leading to a marked decrease in kynurenine levels. This in turn inhibited the development of metastasis and further enhanced antitumor immunity. Indeed, targeting glutamine metabolism rendered checkpoint blockade-resistant tumors susceptible to immunotherapy. Overall, our studies define an intimate interplay between the unique metabolism of tumors and the metabolism of suppressive immune cells.
Keywords: nádorové mikroprostředí; Male; Mice, Knockout; myši inbrední BALB C; Oncology; Neoplasms, Experimental; mužské pohlaví; Immunology; Mice, Inbred BALB C; Innate immunity; myši knockoutované; Immunotherapy; myeloidní supresorové buňky; Animals; buněčná imunita; experimentální nádory; glutamin; ženské pohlaví; Glutamine; zvířata; makrofágy; Immunity, Cellular; imunoterapie; myši; Mice; Female; Macrophages; Tumor Microenvironment; Cancer immunotherapy; Myeloid-Derived Suppressor Cells